Techniques and Steps of Islamic Education Learning Development: Integration of Islamic Values in Learning: Teknik dan Langkah-Langkah Pengembangan Pembelajaran PAI: Integrasi Nilai-Nilai Islam Dalam Pembelajaran - Hidayat, Tatang; Rizal, Ahmad Syamsu; Abdussalam, Aam; Istianah, Istianah (Universitas Muhammadiyah Sidoarjo, 2023)
The reality of learning in the materialism education system eliminates religious values that cause dry learning of divine values. The purpose of this study was to determine the techniques and steps of developing PAI learning through the integration of Islamic values in learning. This research uses a qualitative approach and literature study method. Data retrieval techniques come from primary sources and secondary sources with 6 months of searching for references. Data analysis technique with data interpretation. Based on the results of the discussion, learning is an art and science. Learning is a process of issuing all efforts both materials, methods, and media for the creation of systematic learning and teaching activities starting from planning, implementation, and evaluation to enable students to achieve learning objectives effectively and efficiently. The purpose of learning is to foster humans to be able to optimize their potential (jasadiyyah, aqliyyah, and ruhiyyah) in an integrative and comprehensive manner so as to increase the growth of innovative, creative thinking, proactive communication which includes activities of creativity, reflectivity, reciprocity, and responsibility arranged in appropriate systematic steps in the learning process. The results of this study have implications for the techniques and steps for developing PAI learning by integrating Islamic values in learning.